EL CÍRCULO Y EL LABERINTO: APROXIMACIÓN A EN EL SÉPTIMO CÍRCULO, DE DANIEL GALLEGOS - Víquez Jiménez, Alí (2013)
This article discusses the relationship of the play En el séptimo círculo with Dante's Comedy and delves into thedescription of violence as conceived by Daniel Gallegos in this text.